Double love - William, Kate.; Pascal, Francine (New York : Bantam, 1991)
Jessica connives to steal Todd Wilkins, Sweet Valley High's star basketball player, away from her twin sister Elizabeth.
Booklist.
School Library Journal.
6.0
5-8
Keywords: Family life -- Fiction; High schools -- Fiction; Twins -- Fiction; Family life -- Fiction; High schools -- Fiction; Twins -- Fiction